Navigating the trade-offs between economic growth and environmental sustainability: A global analysis of long-term trends and strategic policies - Kankanam Pathiranage, Heshan Sameera (Taylor & Francis Group, 2024)
The complex relationship between economic growth and environmental sustainability remains one of the most pressing global challenges in the context of climate change. This study offers a comprehensive analysis of these trade-offs by leveraging a dynamic panel dataset spanning 170countries from 2000 to 2020. Using advanced econometric methods, including dynamic panel data models and clustering techniques, this research rigorously tests the Environmental Kuznets Curve hypothesis while exploring the persistence of CO2 emissions and the role of renewable energy in mitigating environmental damage. The key findings indicate that a 1% increase in GDP leads toa 0.42% rise in CO2 emissions, highlighting the entrenched environmental costs of growth, particularly in developing and emerging economies. While renewable energy consumption is negatively correlated with emissions, it has yet to achieve the scale required to significantly offset this growth. Cluster analysis uncovers distinct sustainability profiles, revealing that high-GDP economies continue to face challenges in decoupling growth from emissions, while low-GDP countries show smaller carbon footprints but struggle with scaling renewable technologies. These insights demand differentiated policy strategies: advanced economies must accelerate decarbonization and clean energy innovation, while developing nations should prioritize leapfrogging to renewable technologies with international support. This study contributes to the global debate on sustainability by providing actionable policy recommendations aligned with the Paris Agreement, emphasizing the need for stronger international financial flows to assist low-income countries in achieving sustainable development.